2017
DOI: 10.4103/1117-6806.199966
|View full text |Cite
|
Sign up to set email alerts
|

Systemic assessment of patients undergoing dental implant surgeries: A trans- and post-operative analysis

Abstract: Background:Procedure-related and patient-related factors influence the prognosis of dental implants to a major extent. Hence, we aimed to evaluate and analyze various systemic factors in patients receiving dental implants.Materials and Methods:Fifty-one patients were included in the study, in which a total of 110 dental implants were placed. Complete examination of the subjects was done before and after placement of dental implants. Implant surgery was planned, and osseointegrated dental implants were placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In addition, post-operative swelling is another factor that may influence postsurgery experience as most patients fear this, especially in the facial region where aesthetics is paramount. Similar to this study, Sanjay et al [38] reported mild swelling post implant surgery. Only one of the participants (3.7%) in the present study experienced significant swelling than expected.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, post-operative swelling is another factor that may influence postsurgery experience as most patients fear this, especially in the facial region where aesthetics is paramount. Similar to this study, Sanjay et al [38] reported mild swelling post implant surgery. Only one of the participants (3.7%) in the present study experienced significant swelling than expected.…”
Section: Discussionsupporting
confidence: 88%
“…Dental implants are routinely used in the rehabilitation of tooth loss. Dental implants are often described as a root form that is made of titanium and placed in the position of the natural tooth 1. A number of surgical procedures are performed to insert the dental implants into the bone and to uncover them after completing the osseointegration.…”
mentioning
confidence: 99%